Pengaruh Debt To Asset Ratio, Inventory Turnover,Gross Profit Margin Terhadap Financial Distress Pada Perusahaan Sub Sektor Logam Dan Sejenisnya Yang Terdaftar Di Bei - Cindy Delvia; Qahfi Romula Siregar (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
This study aims to find out how the influence of Debt To Asset Ratio, Inventory Turnover, Gross Profile Margin variables on Financial Distress both partially and simultaneously in Metal and Similar Subsector Companies Listed on the IDX. This research approach is associative. The population is 17 companies and the sample is 7 companies in the Metals and the Like Subsector which are registered on the IDX using a purposive sampling technique. The observation period was carried out for 5 years, starting from 2017 to 2021. The data used is secondary data, namely data obtained directly in the form of financial reports obtained from the website www.idx.co.id. Data analysis techniques were performed using statistical analysis, namely: multiple linear regression analysis, classic assumption test, hypothesis testing and coefficient of determination with SPSS 25.0 for window. The results of this study indicate that partially the Debt To Asset Ratio has no effect on financial distress, Inventory Turnover has no effect on financial distress while Gross profit Margin has an effect on financial distress in Metal Subsector Companies and the like listed on the IDX. Simultaneously has a significant influence on financial distress in Metals and the Like Subsector Companies listed on the IDX.